Patient Expectations on How Doctors Deliver Bad News (Case Study of Cancer Patients in Jambi City) - Ganiem, Leila Mona; Hasanah Suryani Utami (Publisher Cv. Inara, 2021)
Abstract: Research related to patient expectations has existed, but not specifically in Indonesia, especially in Jambi. For this reason, this study is aimed, firstly, to find out the patient's opinion on how doctors deliver bad news according to the SPIKES stage. The second objective was to explore patients' opinions regarding their expectations about the way doctors communicate bad news, namely cancer diagnosis and prognosis in breast cancer patients, taking into account the SPIKES protocol. This case study research uses a qualitative approach. Research in the city of Jambi in January - November 2019, used interviews with eight informants, namely female patients who saw an oncologist (cancer). Interviews were conducted with each informant and also to the group. Doctors only use some stages, namely stages, interview, giving knowledge, strategy, and summary. The patients studied think that the doctor passes through stages, perception, and invitation. There was a large tendency in the Emotions with the empathic response stage, patients who felt that they were given attention to the patient's emotional condition with an empathetic response, only a small proportion did not feel the doctor's empathic response. Expectations of patients, doctors pay attention to the stages of SPIKES as well as the dimensions of content and dimensions of relationships in delivering bad news about a diagnosis of the disease.